2014
DOI: 10.1371/journal.pone.0092248
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Lung Tumor Microenvironment Modulates Therapeutic Compound Responsiveness In Vitro – Implication for Drug Development

Abstract: Three-dimensional (3D) cell culture is gaining acceptance in response to the need for cellular models that better mimic physiologic tissues. Spheroids are one such 3D model where clusters of cells will undergo self-assembly to form viable, 3D tumor-like structures. However, to date little is known about how spheroid biology compares to that of the more traditional and widely utilized 2D monolayer cultures. Therefore, the goal of this study was to characterize the phenotypic and functional differences between l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 66 publications
(80 reference statements)
9
144
0
4
Order By: Relevance
“…Thus, these results might qualify spheroids as proper models to recapitulate specific subsets of cancer metastasis. Nevertheless, comprehensive systematic investigations on phenotypic changes, potentially altered signaling pathways and the response to drug treatment in 2D vs 3D systems have only occasionally been performed (Ekert et al, 2014;Luca et al, 2013;Pickl and Ries, 2009). We focused on colon carcinoma, being the third most deadly cancer in the world, to thoroughly evaluate the main signaling pathways in 2D vs 3D spheroid cultures under normal and treated conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these results might qualify spheroids as proper models to recapitulate specific subsets of cancer metastasis. Nevertheless, comprehensive systematic investigations on phenotypic changes, potentially altered signaling pathways and the response to drug treatment in 2D vs 3D systems have only occasionally been performed (Ekert et al, 2014;Luca et al, 2013;Pickl and Ries, 2009). We focused on colon carcinoma, being the third most deadly cancer in the world, to thoroughly evaluate the main signaling pathways in 2D vs 3D spheroid cultures under normal and treated conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, only a few comprehensive and systematic studies have been found that compare distinct signaling pathways in 2D vs 3D culture, in the presence or absence of ECM and/or stromal cells, or upon treatment with inhibitors (Ekert et al, 2014;Luca et al, 2013;Pickl and Ries, 2009). Changes in signaling cascades in cancer cells or crosstalk with other cell types in 3D cultures are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Heterotypic MSs more closely mimic the heterogeneity of tumors and the heterotypic inter-relations between cells, and, in addition to monotypic culture, they allow the investigation of important tumor endpoints such as angiogenesis, tumor cell migration and invasion, and drug responsiveness [101]. Examples of heterotypic spheroids may encompass tumor cells with fibroblasts, macrophages, and endothelial cells [102,103]. For example, heterotypic MSs of melanoma cell lines and endothelial cells allowed to demonstrate that invasion and angiogenesis processes may be potentiated by cadherins [104].…”
Section: D Tumor Modelsmentioning
confidence: 99%
“…Importantly, the lack of a 3D environment, or even the absence of appropriate cell anchorage to a 2D surface, can cause abnormalities in 2D primary cell function that essentially eliminate the potential advantages of adopting a primary cell-culture model in the first place (77). There are now numerous examples of the use of a 3D microenvironment as the crucial element in improving in-vitro disease models for cancer research and nanotoxicology, and these increasingly offer a meaningful alternative to ethically-unattractive animal testing, as well as a physiologically-relevant advance over conventional 2D culture models (78)(79)(80)(81)(82)(83)(84)(85). As an example, in case of cancer cells, a key characteristic is their acquisition of resistance to a variety of anticancer drugs through a variety of mechanisms.…”
Section: In Vitro Systems: 2d Vs 3dmentioning
confidence: 99%